Poly(ionic liquid)s as lubricant additives with insight into adsorption-lubrication relationship. (January 2022) - Wu, Jian; Luo, Yanlong; Chen, Yifeng; Lu, Xiaohua; Feng, Xin; Bao, Ningzhong; Shi, Yijun
Abstract: Ionic liquids (ILs) are very potential lubricant additives for their strong adsorption and tribochemical reactions at the interface. In this work, poly(ionic liquid) of PImC6 NTf2 is used as lubricant additive in base oil of PEG, which can reduce the wear volume by around 65 times under 2.5 GPa. The lubricity is much more advantageous than the geminal dicationic IL of BIm5 -(NTf2 )2 . The adsorption strength of lubricants is studied by employing the microcalorimeter to evaluate the adsorption heat, AFM to test the adhesion force, and molecular dynamics simulation to calculate the interfacial binding energy. As a result, the adsorption strength of PImC6 NTf2 is obviously higher than BIm5 -(NTf2 )2, and the lubricity is strongly dependent on the adsorption strength of ILs. Highlights: Poly(ionic liquid) (PIL) of PImC6 NTf2 is used as lubricant additive in PEG. The wear volume is reduced by around 65 times comparing with PEG. The lubricity of PImC6 NTf2 is better than the geminal dicationic IL of BIm5 -(NTf2 )2 . The adsorption strength is studied by microcalorimeter, AFM and MD simulation. The lubrication of ILs/base oil is strongly dependent on the adsorption of ILs.